Greek Tragedy for the New Millenium: Public Testimony and Restorative Justice in Yael Farber’S Molora - Dugdale, Eric (Classica - Revista Brasileira de Estudos Clássicos, 2013)
This paper examines Molora, an adaptation of the Orestes story by South African playwright Yael Farber set in the context of South Africa’s Truth and Reconciliation Commission. It considers the play’s engagement with restorative justice in relation to the exploration of different forms of justice by Aeschylus in his Oresteia. It also examines Farber’s play in light of the ideas of the influential Brazilian theatre director Augusto Boal, noting how the relationship with the classical past has changed in the three decades between the publication of Boal’s Teatro del oprimido y otras poéticas políticas in 1974 and the première of Farber’s Molora in 2003.